Antimycobacterial activity of synthetic compounds isolated from South African medicinal plants against mycobacterium tuberculosis - Ledwaba, Elizabeth Ramadimetsa (Vaal University of Technology, 2014)
Tuberculosis (TB) remains one of the most difficult infectious diseases to control in the world today. The disease spreads easily in overcrowded, badly ventilated places and among people who are undernourished. Trends in the incidence of TB together with the development of multi-drug (MDR-TB) and extensively drug resistant (XDR-TB) strains of TB raises the need to intensify the search for more efficient drugs to combat this disease. Herbal remedies used in traditional medicine provide an interesting and largely unexplored source for the discovery of potentially new drugs for infections such as TB. The aim of the study was to evaluate the in vitro antimycobacterial activity of synthesized compounds from medicinal plants against Mycobacterium tuberculosis (M. tuberculosis). About 40 synthesized compounds isolated from South African medicinal plants were screened against H37RV using microplate alamar blue assay (MABA). Identified active compounds were screened against resistant strains of M. tuberculosis (MDR, XDR and pre-XDR) and sensitive clinical isolates of TB. Cytotoxicity and synergistic drug combination studies were done on active compounds to validate their toxicity and synergy levels. Cytotoxicity was done by sulforhodamine assay (SRB) against the C2C12 cell line. Only six compounds showed activity against M. tuberculosis with minimum inhibitory concentration (MIC) below 10μg/ml. The results obtained indicated that the cytotoxicity effects of the three compounds on C2C12 cells demonstrated marginal toxicity except for MVB 282/61215 which showed a high toxicity at the lowest concentration of 0.156μg/ml with over 100% viable cells at the highest concentration (5μg/ml). MVB 282/61271 had the highest percentage cell viability (65%) at the lowest concentration. Only two compounds had a higher potency evoking a bigger response at low concentrations with treated cells still viable after 3 days of incubation with the compound which was comparable with the treatment of isoniazid (INH). Synergistic activity of the six compounds was less in INH combination as compared to the rifampicin’s (RIF) combination. The results demonstrated that the synergistic interaction between the compounds and RIF could the antituberculosis acitivity. In conclusion the synergistic effects with RIF translate to lower dosing requirements of the compounds and the potential to combat multidrug resistant TB. In deed there is no doubt that natural products, with their range of interesting chemical structures and powerful antimycobacterial effects are certain to remain important participants in the development of new generations of antimycobacterial drugs.
M. Tech. (Department of Health Sciences, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Tuberculosis (TB); Mycobacterium tuberculosis (M. tuberculosis); Antimycobacterial; Synthetic compounds; Cytotoxicity; Synergistic; Medicinal plants; Dissertations, Academic -- South Africa.; Mycobacterium tuberculosis.; Medicinal plants -- South Africa.